2014
DOI: 10.1371/journal.pone.0091940
|View full text |Cite|
|
Sign up to set email alerts
|

NTRK1 Fusion in Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) is the most aggressive form of brain tumor, yet with no targeted therapy with substantial survival benefit. Recent studies on solid tumors showed that fusion genes often play driver roles and are promising targets for pharmaceutical intervention. To survey potential fusion genes in GBMs, we analysed RNA-Seq data from 162 GBM patients available through The Cancer Genome Atlas (TCGA), and found that 3′ exons of neurotrophic tyrosine kinase receptor type 1 (NTRK1, encoding TrkA) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 30 publications
2
74
2
Order By: Relevance
“…No TRKA inhibitors were explored in clinical trials with the possible exception of lestaurtinib (CEP-701), a staurosporine-derivative multikinase inhibitor that was investigated in clinical settings with reported TRKA overexpression, without evidence of efficacy (7,38). However, recent studies that have identified recurring oncogenic NTRK1 rearrangements in subsets of NSCLC and colorectal carcinoma patients (11,12), as well as other studies suggesting a potential role of activated TRKA in other tumor types, including glioblastoma and Spitz melanoma (14)(15)(16)39), have created much renewed interest in the identification and clinical investigation of effective TRKA inhibitors (13). In a rapidly evolving scenario, these findings indicate that TRKA inhibition may represent an innovative opportunity for the therapy of selected patients whose tumors harbor NTRK1 gene rearrangements and this has supported the enrollment of TRKA-positive patients in ongoing clinical trials of entrectinib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No TRKA inhibitors were explored in clinical trials with the possible exception of lestaurtinib (CEP-701), a staurosporine-derivative multikinase inhibitor that was investigated in clinical settings with reported TRKA overexpression, without evidence of efficacy (7,38). However, recent studies that have identified recurring oncogenic NTRK1 rearrangements in subsets of NSCLC and colorectal carcinoma patients (11,12), as well as other studies suggesting a potential role of activated TRKA in other tumor types, including glioblastoma and Spitz melanoma (14)(15)(16)39), have created much renewed interest in the identification and clinical investigation of effective TRKA inhibitors (13). In a rapidly evolving scenario, these findings indicate that TRKA inhibition may represent an innovative opportunity for the therapy of selected patients whose tumors harbor NTRK1 gene rearrangements and this has supported the enrollment of TRKA-positive patients in ongoing clinical trials of entrectinib.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a rapidly evolving landscape, large-scale sequencing efforts have led to identification of additional chromosomal rearrangements involving NTRK1 as well as NTRK2 and NTRK3, the genes which respectively encode the TRKA, TRKB, and TRKC proteins, in further tumor types (14)(15)(16)(17). These findings provide a strong rationale for the development of TRK kinase inhibitors in several distinct selected patient populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these findings suggest that tumor cells with different NTRK1 fusion partners acquire TRK inhibitor resistance, at least in part, by common mutations that induce drug resistance. Previous studies have showed that entrectinib is clinically effective for tumors expressing NTRK1 fusion products, including NSCLC expressing SQSTN-NTRK1, glioneuronal tumors expressing BCAN-NTRK1, and colon cancer expressing LMNA-NTRK1 (5,6,39). However, almost all responders suffered from recurrent diseases due to drug resistance (5,6,39).…”
Section: Discussionmentioning
confidence: 99%
“…2). At least four NTRK1 fusion partners, such as LMNA, TPM3, SQSTM1, and BCAN, have been reported (3)(4)(5)(6). The NTRK1 fusion gene products promote signal transduction through the PI3K-AKT, PLCg-PKC, and SHC-RAS-MAPK signaling pathways and play crucial roles in cell survival (7).…”
Section: Introductionmentioning
confidence: 99%